일본의 도시재생 사업방식에 관한 고찰 - 김준환(Kim, Joon Hwan) (대한부동산학회지, 2018)
본 연구는 한국보다 10여년 이상 앞서 도시재생사업을 추진하고 있는 일본의 도시재생사업의 구조를 파악하고, 현재 추진하고 있는 도시재생 사업방식에 대한 분석을 통해 한국의 도시재생 사업방식에 대한 방향성을 제시하고자 한다.연구결과 첫째, 일본의 도새재생 사업방식은 도시의 규모와 특성 등에 의해 크게 3가지 방식으로 추진되고 있는 것으로 나타났다. 둘째, 대도시 지역의 경우 도시재생긴급정비지역과 특정도시재생긴급정비지역 내에서 “민간의 활력을 중심으로 한 도시재생사업”이 추진되고 있는 것으로 나타났다. 셋째, 일상생활의 질 향상과 지역경제 및 사회 활성화를 도모하는 것을 목적으로 시촌무라와 민간을 포함한 다양한 주체에 의해 구성된 조직과 국가의 지원에 의해 “관민의 공공·공익시설정비 등에 의한 전국도시재생사업”이 추진되고 있는 것으로 나타났다. 넷째, 도시의 경영이 어려운 지방 중소도시의 경우에는 도시계획구역 내의 구역에 대해 주택 및 도시기능 증진시설의 입지 적정화를 도모하기 위해 작성된 “입지적정화계획”에 의해 “토지이용유도 등에 의한 콤팩트시티(집약도시) 정비사업” 이 추진되고 있는 것으로 나타났다. This study aims to the structure of Japanese Urban Regeneration projects, which have been executed at least 10 years earlier than those of Korea, and, thereafter, to provide proper development directions of urban regeneration projects in Korea.Thereafter, this study could draw following conclusions:(1) Japanese urban regeneration project types could be divided into three categories by the size and characteristics of the city. (2) In case of metropolitan cities, "Urban regeneration projects, driven by private vitalities" were found to be under progress in urgent urban maintenance areas as well as special urgent urban maintenance areas. (3) It was also found that "National Urban Regeneration Projects of public interest facilities maintenance, led by organizations, composed of diverse entities including local autonomous entity and private parties, and the state subsidies in order to improve the quality of everyday life and to promote the social revitalization. (4) Finally, in case of small/medium-dsized cities,where urban management are actually in absence, "Compact City Redevelopment Projects by Land Use Guidance" were being implemented in accordance with the "Locational Rationalization Plans" in order to promote the locational retionalization of residential and other urban functional facilities as to the districts of urban planning zones. KCI Citation Count: 5